Cooperação processual : efetividade do devido processo legal e o propósito da decisão de mérito célere, justa e efetiva - Borges, Patrícia Almeida Campos (2021)
The democratic rule of law guarantees everyone the fundamental right to a fair, due, and swift process, and, in this respect, there is a need for procedural rules to be subject to constitutional values and principles, especially those that are closely related to fundamental rights and guarantees. The principle of cooperation introduces a new culture in the legal environment, leading to reflection on each one's share of responsibility in the course of the proceedings. One can no longer relegate the responsibility for the delivery of the jurisdictional activity solely to the State-judge; however, it must encourage the parties to act in a collaborative manner, under penalty of flagrantly violating a fundamental constitutional right. Thus, in the face of the constitutional model of participatory procedure, this paper aims to clarify the importance of mutual cooperation between the subjects involved in the judicial process so that it is fast, due and fair, as well as identify the ways and means by which the procedural adjective law directs the parties and the judge to the duty of cooperation, especially in the civil procedural phase of knowledge, when the allegations of the parties are put forward and the facts are proved.